1993
DOI: 10.1002/anie.199314671
|View full text |Cite
|
Sign up to set email alerts
|

Rotation about the CSe Bond as the Rate‐Determining Step in the Racemization of α‐Selenium‐Substituted Alkyllithium Compounds

Abstract: New possibilities for increasing the stability of the configuration of α‐heteroatomsubstituted alkyllithium compounds follow from the unexpected finding that ortho methyl groups influence the rate of racemization of α‐arylselenoalkyllithium compounds. According to this observation, rotation about the CX bond (X  Se) [Eq. (a)] can be the rate‐determining step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…The groups of Reich and Hoffmann have also investigated the dynamics of carbanionic inversion in a variety of α-hetero and α,α 1 -dihetero organolithium compounds, where hetero = Te, Si, S, Se, see for example, 18 to 22a−c , both internally and externally solvated. In addition, by use of HMPT as external ligand(s), organolithium species RLi(HMPT) n ( n = 0−4) with different degrees of C−Li bond ionic character were generated and studied.…”
Section: Resultsmentioning
confidence: 99%
“…The groups of Reich and Hoffmann have also investigated the dynamics of carbanionic inversion in a variety of α-hetero and α,α 1 -dihetero organolithium compounds, where hetero = Te, Si, S, Se, see for example, 18 to 22a−c , both internally and externally solvated. In addition, by use of HMPT as external ligand(s), organolithium species RLi(HMPT) n ( n = 0−4) with different degrees of C−Li bond ionic character were generated and studied.…”
Section: Resultsmentioning
confidence: 99%
“…A very different mechanism for the inversion of α ‐heteroatom‐substituted organolithium reagents was reported independently by Hoffmann and co‐workers and by Reich et al in 1993 15, 16. The addition of hexamethyl phosphoramide (HMPA) to organolithium compounds 10 and 11 generates spectroscopically characterizable contact ion pairs (CIPs).…”
Section: Spectroscopic and Chemical Methods For Determining Configmentioning
confidence: 98%
“…Studies by both Hoffmann and co-workers [5960] and by Reich and co-workers [61] showed that the rate determining step for racemisation of α-thio, α-seleno and α-telluroorganolithiums is rotation about the C–S, Se or Te bond [62]. Simple inversion in α-thio-substituted carbanions has a barrier as low as 0.5 kcal·mol −1 [63] making inversion itself unlikely to comprise the rate determining step of the racemisation.…”
Section: Reviewmentioning
confidence: 99%